Crafted Objects Carry Meaning - Pearson, Sarah (Canadian Review of Art Education / Revue canadienne d'éducation artistique, 2025)
This article delves into the aspects which contribute to the creation of an object’s itinerary or life story. In the case for crafted objects this includes material history, maker-object relationships, and the historical narratives surrounding craft practices. The story of crochet samples is related through visual life writing and poetry, to highlight the agents active in the ‘creation’ of objects, as well as the pedagogical potential of undesirable outcomes within craft making and learning.